The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1242/dmm.023176
|View full text |Cite
|
Sign up to set email alerts
|

The goya mutation identifies distinct novel roles for MAP3K1 in cochlear sensory hair cell development and survival

Abstract: Mitogen-activated protein kinase, MAP3K1, plays an important role in a number of cellular processes, including epithelial migration during eye organogenesis. In addition, studies in keratinocytes indicate that MAP3K1 signalling through JNK is important for actin stress fibre formation and cell migration. However, MAP3K1 can also act independently of JNK in the regulation of cell proliferation and apoptosis. We have identified a mouse mutant, goya, which exhibits the eyes-open-at-birth and microphthalmia phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In a parallel study, a splice-site mutation in the Map3k1 gene in goya mutant mice was identified as part of an ENU mutagenesis screening program ( Parker et al, 2015 ). g oya mice also exhibit a progressive hearing-loss phenotype along with the supernumerary OHCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel study, a splice-site mutation in the Map3k1 gene in goya mutant mice was identified as part of an ENU mutagenesis screening program ( Parker et al, 2015 ). g oya mice also exhibit a progressive hearing-loss phenotype along with the supernumerary OHCs.…”
Section: Discussionmentioning
confidence: 99%
“…g oya mice also exhibit a progressive hearing-loss phenotype along with the supernumerary OHCs. Interestingly, when maintained on the same genetic background (C3H), the goya and Map3k1 tm1Yxia mutant mice were found to have a similar progressive hearing-loss phenotype and were profoundly deaf by 9 weeks ( Parker et al, 2015 ). Modulation of the phenotype of a given allele by the genetic background of an inbred strain is a well-documented phenomenon ( Doetschman, 2009 ; Montagutelli, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…XY Map3k1 mPHD/+ mice that are heterozygous for an inactive PHD motif have a significantly enlarged testes but with a reduced number of Leydig cells [Charlaftis et al, 2014]. Another Map3k1 mouse model, goya , exhibits a severe hearing loss [Parker et al, 2015]. This data suggest that in testis determination either the MAP kinase signaling pathways in human or mouse have diverged or the difference in phenotype is caused by an intrinsic difference in the type of mutation.…”
Section: Map3k1mentioning
confidence: 97%
“…Our data point to the activation of MAPK14 as the possible link between the absence of DUSP1 and a premature increase in cochlear oxidative stress and pro-inflammatory status. MAPK14 is expressed in the cochlea (Parker et al, 2015; Sanchez-Calderon et al, 2010) and it is activated at different time points after noise insult (Jamesdaniel et al, 2011; Maeda et al, 2013; Murillo-Cuesta et al, 2015), as well as during ageing (Sha et al, 2009). We show here that DUSP1 is induced by noise-exposure and that its transcription increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…JNK and p38 MAPK transcripts and proteins are expressed in the cochlea from late intrauterine development (Parker et al, 2015; Sanchez-Calderon et al, 2010). They form part of the adult cochlear response to noise insult (Jamesdaniel et al, 2011; Maeda et al, 2013) and to ageing (Sha et al, 2009).…”
Section: Introductionmentioning
confidence: 99%